Pengaruh Kemampuan Kerjasama dan Motivasi Kerja Terhadap Produktivitas Kerja Pada Karyawan CV. Buana Jaya Sentosa: The Effect of Cooperation Skills and Work Motivation on Work Productivity Among Employees of CV. Buana Jaya Sentosa - Rosiana Fitri Rahayu; Mohammad Amas Lahat; Dani Chandra Utama (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Abstracts - This study aims to explain the partial and simultaneous influence between the variables of cooperation ability and work motivation on work productivity at CV. Buana Jaya Sentosa. This type of research is quantitative research because it is related to numbers and statistics to test variables and hypotheses. Data processing using the SPSS Version 22 program with a population of 41 employees of CV. Buana Jaya Sentosa. The data used are primary data by distributing questionnaires via google form to respondents and data analysis using validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, f-tests, t-tests, and determination coefficient tests (R2) partially or simultaneously. From the research results for the variable of cooperation ability, partial significance on work productivity with a calculated t value of 3.044> ttable 2.024 and significant of 0.000 <0.05, then the first hypothesis (H1) is accepted, the work motivation variable has a partial significant effect on work productivity with a calculated t value of 2.194> ttable 1.648 and significant of 0.000 <0.05, then the second hypothesis (H2) is accepted, while the variables of cooperation ability and work motivation have a simultaneous significant effect on work productivity with a calculated f value of 14.899> ftable 3.24 and a significant value of 0.000 <0.05, then the third hypothesis (H3) is accepted